Diagnósticos de enfermagem em pacientes submetidos à hemodiálise: semelhanças entre o modelo de adaptação e a NANDA internacional - Frazão, Cecília Maria Farias de Queiroz (2012)
The nurses in the hemodialysis has an important role in the nursing process implementation, in the context of a theoretical referential. Among the nursing theories, highlights the Roy´s adaptations model, who considers a person as an holistic adaptive system that aims to adapt customers to different living conditions. Thus, it is believed that the Roy´s nursing process will guide nursing care to patients on dialysis. Therefore, the study aimed to analyze the nursing diagnosis present in patients with chronic kidney disease on hemodialysis based on the theoretical model of Roy and NANDA-International. Descriptive and cros-sectional study, performed at a dialysis center in a city in northeastern Brazil. Sample of 178 patients and consecutive sampling by convenience. Data collection ocurred from October/2011 until February/2012, through interview and physical examination forms. Data analysis was initiated by clinical reasoning, diagnosis judgment and similarity relation. Then, the data were entered into SPSS program, 16.0 version, generating descriptive statistics. The project was approved by the Ethics Research Committee (protocol nº 115/11) with a Presentation Certificate for Ethics Appreciation (in 0139.0.051.000-111) and was funded by the Universal edict MCT / CNPq 14/2010. The results revealed that most patients were male (52.2%), married (62.9%) and residents in the Natal´s metropolitan region (54.5%). The mean age was 46.6 years and the years of study, 8,5. Regarding nursing diagnosis obtained an average of 6.6, especially: Risk of Infection (100%), excessive fluid volume (99.4%) and hypothermia (61.8%). On the other hand the adaptive problems average was 6.4, and the most common: intracellular fluid retention (99.4%); Hyperkalemia (64.6%); Hypothermia (61.8%) and edema (53.9%). Were established 20 similarity relations between the NANDA-International nursing diagnosis and adaptive problems of Roy, namely: risk of falls / injury risk and potential for injury, impaired physical mobility and walking mobility and / or restricted coordination, dressing self-care deficit and loss of self-care ability; hypothermia and hypothermia; impaired skin integrity and impaired skin integrity; excessive fluid volume and intracellular fluid retention / Hyperkalemia / Hypocalcemia / edema; imbalanced nutrition: less than body requirements and Nutrition less than the body's needs; constipation and constipation, acute pain and acute pain, chronic pain and chronic pain, sensorial perception disturbed: visual, tactile and auditory disabilities and a primary sense: sight, hearing and tactile; sleep deprivation and insomnia, fatigue and intolerance to activities; ineffective self health and fails in the role; sexual dysfunction and sexual dysfunction; situational low self-esteem and low self-esteem, and diarrhea and diarrhea. We conclude that there is similarity between the typologies and was required a model´s analysis, because they present different ways to establish the nursing diagnosis. Moreover, the nursing process use, under the context of a theory and a classification system, subsidizes the care and contributes to the strengthening of nursing science